Effectiveness of Aquatic Therapy in Autism Spectrum Disorders - Saman Shaukat; Muhammad Furqan Hassan; Qurat Ul Ain Khalid; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2026)
Autism spectrum disorder (ASD) is a neurodevelopmental condition characterised by repetitive or restricted behaviours and social communication deficits. The reported cases are on the rise. In recent years, sensorybased physical activity programmes have been incorporated into therapeutic practices for children with ASD. Among these, aquatic therapy is a multimodal intervention integrating sensory, social and motor components in a structured environment. To reduce the physical burden of movement, these water-based interventions utilize properties like buoyancy, resistance and hydrostatic pressure. Recent literature suggests that aquatic therapy can be an effective adjunct in the management of ASD, especially in enhancing social participation and motor skills. However, therapists' training and standardization in protocols need further exploration. This mini review discusses the various kinds of aquatic therapy and explores the evidence for the integration of aquatic therapy in clinical and educational settings for children and adolescents with ASD. Keywords: Autism Spectrum Disorder, Aquatic Therapy, Motor Skills, Multimodal Treatment, Neurodevelopmental Disorders, Social Behavior.